Imitation and the evolution of Walrasian behavior: theoretically fragile but behaviorally robust - José Apesteguia; Steffen Huck; Jörg Oechssler; Simon Weidenholzer (Center for Economic Studies and ifo Institute (CESifo), 2008)
A well-known result by Vega-Redondo (1997) implies that in symmetric Cournot oligopoly, imitation leads to the Walrasian outcome where price equals marginal cost. In this paper, we show that this result is not robust to the slightest asymmetry in fixed costs. Instead of obtaining the Walrasian outcome as unique prediction, every outcome where agents choose identical actions will be played some fraction of the time in the long run. We then conduct experiments to check this fragility. We obtain that, contrary to the theoretical prediction, the Walrasian outcome is still a good predictor of behavior.
Keywords: C72; C91; C92; D43; L13; 330; evolutionary game theory; stochastic stability; imitation; Cournot markets; information; experiments; simulations; Imitationswettbewerb; Evolutionäre Spieltheorie; Oligopol; Allgemeines Gleichgewicht; Test; Theorie